Leishmaniasis: A Menace - Alam, Mohammad Mumtaz (International Journal of Pharmaceutical & Biological Archive, 2017)
Leishmanisis is a disease caused by protozoan parasites of genus Leishmania which gets spread by the bite of female phlebotomine sandfly. This may be presented in patients in the form of either visceral leishmaniasis or post kala-azar or dermal leishmaniasis or cutaneous or mucocutaneous. More than 20 species of Leishmania are responsible for causing infections in humans. Unfortunately, the affected regions are often remote and unstable, with limited resources for targeting this deadly disease. The most effective diagnostic tests for leishmaniasis are invasive, potentially dangerous and samples are required from spleen, lymph nodes or bone marrow. Additionally, such diagnostic tests are not readily available in resource-poor and endemic areas. Different treatment options are available for treatment of this disease, with varying effectiveness and adverse effects. The paper herein highlights the problem of leishmaniasis along with diagnostic options available, currently used drugs and different agents in the stage of preclinical and clinical development.